Numerical Study and Comparison of Heat and Mass Transfer Fluid Flow of Silver and Aluminum Oxide Nanofluid Past a Horizontally Plate - Rani, M. Selva (Research Updates in Mathematics and Computer Science Vol. 2, 2024)
This work analyses the behavior, characteristics, flow development, and heat and mass transfer coefficient of nanofluids under laminar boundary layer flow over a horizontally inclined plate. A nanofluid is the suspension of ultrafine particles in a base fluid, which tremendously enhances the heat transfer characteristics of the original fluid. This work aims to compare the characteristics between two different nanofluids Silver and Aluminum Oxide with the same base fluid water under the heat and mass transfer nanofluid past a horizontally inclined plate. The Basic governing equations of the free convective flow for heat and mass transfer are converted to a non-dimensional partial differential equation using non-dimensional parameters and are solved numerically using crank Nicolson Implicit finite difference method. The final equations are solved using the MATLAB software and the results are shown as graphs. The velocity, temperature and concentration profiles are illustrated graphically to study about the various parameters Grashof Number, Angle of inclination, Nano particle volume fraction, Schmidt number and non-uniform surface temperature.